Characteristic and Diversity Vegetation of Bukit Tiga Puluh National Park as Dietary Sources for Reintroduced Sumatran Orang Utan (Pongo abelii Lesson) - Wanda Kuswanda; Sriyanti P. Barus (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2019)
The population of Sumatran orang utan in natural habitat has been declined and threatened with extinction. The orang utanreintroduction program is expected to increase breeding and population in nature. This study aimed to analyze the important value index of vegetation as well as the diversity and abundance species of Bukit Tiga Puluh National Park (BTNP) as dietary sources for reintroduced Sumatran orang utan. The research was conducted during two years from 2015 to 2016. The data collection for flora characteristics is done through the vegetation analysis with strip transects method. Plots were selected by stratification method based on the resort management and the land cover, like primary and secondary forests. Total flora species on a plot of 2.8 ha were identified about 301 species. The highest variation found in Suo-Suo Resort (139 species) and the lowest in Talang Lakat Resort (82 species). The dominant species have been found were Eugenia grandiflora O. Berg, Macaranga lowii King ex Hook.f., Shore iliginosa Foxw., and Tarrietia rubiginosa Kostern. Vegetation chararacteristic to be identified were tree density of 350-552.5 individuals/ha, species diversity index of 2.86-4.19, and abundance index of 32.1087.35. It also identified that vegetation characteristic among resort and land cover were different (p <0.05). Moreover, there were about 110 species of tree plants including of 31 families that found as dietary sources for orang utan and leaves became the highest plant parts which consumed by orang utans (41.8%) compared to other parts. Based on area size, ecosystem types as well as vegetation composition and variation, BTNP may support the increasing population of orang utans. However, there needs to be considered that other aspects such as high human activity within the conservation area, particularly by Talang Mamak tribe communities, may cause unsuccessful achievement on reintroduction program of orang utan.